2019
DOI: 10.1093/jhps/hnz011
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory of clinical outcomes following hip arthroscopy in female subgroup populations

Abstract: To describe the recovery trajectory in a group of relatively older borderline dysplastic female femoroacetabular impingement syndrome (FAIS) patients following arthroscopic surgery, to determine if outcomes in this group differs from females with different age and bony morphology characteristics. Four subgroups were created to define (i) older females (>35 years), borderline dysplastic (lateral center edge angle [LCEA] ≤ 25 degrees) and anterior wall index (AWI) deficient (AWI ≤ 0.40) (older, borderline dyspla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Previous studies have examined recovery after hip arthroscopy using pain and validated PROs and found significant improvement occurring in the first 3 months, with a majority of patients achieving a clinically significant outcome at 1- and 2-year follow-up. 8,34 Patient factors such as older age, female sex, and elevated body mass index (BMI) have been associated with worse postoperative outcomes. 16 Similarly, preoperative factors such as preoperative narcotic use, workers’ compensation status, higher lateral center-edge angle, and osteoarthritic changes have been shown to predict negative outcomes, and response to intra-articular injections has been shown to be a predictor of positive outcomes.…”
mentioning
confidence: 99%
“…Previous studies have examined recovery after hip arthroscopy using pain and validated PROs and found significant improvement occurring in the first 3 months, with a majority of patients achieving a clinically significant outcome at 1- and 2-year follow-up. 8,34 Patient factors such as older age, female sex, and elevated body mass index (BMI) have been associated with worse postoperative outcomes. 16 Similarly, preoperative factors such as preoperative narcotic use, workers’ compensation status, higher lateral center-edge angle, and osteoarthritic changes have been shown to predict negative outcomes, and response to intra-articular injections has been shown to be a predictor of positive outcomes.…”
mentioning
confidence: 99%
“…Study population consisted of all consecutive patients with FAIS, derived from the orthopedic outpatient department from the two participating hospitals. Inclusion criteria were age between 18–65 years, a physical and radiological examination that confirms FAIS without severe osteoarthritis (≥Tönnis grade 3) [ 9 ], conservative treatment of FAIS of at least 6 months and physical activity. Exclusion criteria were patients with prior surgery to the hip for FAIS, a pathological fracture of the hip or other metastatic pathology and patients not speaking the Dutch language or refusing to participate.…”
Section: Methodsmentioning
confidence: 99%
“…15,[18][19][20][21][22] Seven additional studies presenting associations between LCEA and PRO measures were identified but provided insufficient data to be included in a meta-analysis. [23][24][25][26][27][28][29] All associations for which there was insufficient data to perform meta-analysis are listed in Supplemental Table 4 (http://links.lww.com/JAAOS/A849). These studies were excluded as, for each PRO, there were fewer than the minimum three studies required for quantitative synthesis reporting data in the same format-such as odds ratios or mean 6 SD-thus prohibiting meta-analysis.…”
Section: Study Selectionmentioning
confidence: 99%